Activity-based working: How the use of available workplace options increases perceived autonomy in the workplace. - Becker, Cathrin; Soucek, Roman; Göritz, Anja S. (Work, 2022)
BACKGROUND: If companies are building offices, nowadays, they mostly realize activity-based concepts as a response to growing flexibility requirements of a digitalized society. Activity-based concepts provide multiple workplace options to employees. After moving to new workspaces, employees need to get used to the facilities and learn how to use the available workplace options. OBJECTIVE: The effectiveness of activity-based working relies on the workplace options and on employees' autonomy to use them according to their current work tasks. The present study examined the change in the use of workplace options, task-environment fit, and autonomy in the workplace after the implementation of an activity-based working concept. METHODS: The study was longitudinal with two time points (Time 1 and Time 2) that were one year apart. Data were obtained prior to the COVID-19 pandemic. The sample consisted of 153 employees working in activity-based office environments in two organizations in Germany. The average age was 45 years (SD = 11); 44% were men; and 23% had leadership responsibilities. RESULTS: The increased use of available workplace options offered in activity-based working concepts was associated with better task-environment fit, which in turn led to an increase in perceived autonomy in the workplace. CONCLUSIONS: The results support the core idea of activity-based working and revealed how this office concept unfolds its effectiveness: Having different workplace options available and using them led to a higher perceived task-environment fit, which in turn, contributed to a higher perceived autonomy in the workplace.